The Effectiveness of Referral Back Sheets on Early Detection of High Maternal Risk in the Work Area of Subang Health Department - Septiani, Leri; Herawati, Yanti; Wijayanegara, Hidayat; Hartiningsih, Siti Sugih (Global Writing Academica Researching & Publishing, 2023)
Maternal health is an important aspect of the health care system, as the quality of maternal health has a direct impact on the well-being of the mother and her unborn child. High maternal risk refers to conditions that increase the potential for complications during pregnancy, labor and postpartum. Early identification of high maternal risk is crucial to provide appropriate care and reduce the risk of complications that can harm both mother and baby. One tool that can be used to support early detection of high maternal risk is the Pre-Referral Back Sheet (PRBS). PRBS is an instrument that presents a collection of questions or certain parameters that must be filled in by health workers, especially midwives during prenatal examinations. It is designed to identify risk factors and early symptoms that may indicate potential maternal high risk. Although the LBPR has been integrated into maternal health care practice, no in-depth study has specifically evaluated its effectiveness in early detection of maternal high risk. Therefore, this study aimed to evaluate the effectiveness of the Pre-Referral Back Sheet in early detection of maternal high risk and identify the extent to which this tool can improve the quality of maternal health care. This study used an observational method with a cross-sectional approach with a sample of 450 pregnant women who attended prenatal examinations at selected health centers. Of the total 450 respondents, the majority were pregnant women of reproductive age (20-35 years) with an average age of 28 years. 60% of respondents had secondary education, and 80% lived in urban areas. The prevalence of maternal high risk in the Subang Health Office Working Area was found to be 18%, based on the criteria identified by the LBPR. Statistical analysis showed that the use of LBPR significantly improved early detection of maternal high risk. The sensitivity of LBPR reached 75%, with a specificity of 85%. These results indicate that the LBPR can identify most maternal high-risk cases with good accuracy. Based on these findings, it can be concluded that the Pre-Referral Back Sheet (LBPR) is effective in early detection of maternal high risk in the Subang Health Office Working Area. The use of LBPR can improve the quality of maternal health services and contribute positively to efforts to prevent and manage high maternal risk.